2023
DOI: 10.1111/2041-210x.14040
|View full text |Cite|
|
Sign up to set email alerts
|

Scale dependency of lidar‐derived forest structural diversity

Abstract: Lidar‐derived forest structural diversity (FSD) metrics—including measures of forest canopy height, vegetation arrangement, canopy cover (CC), structural complexity and leaf area and density—are increasingly used to describe forest structural characteristics and can be used to infer many ecosystem functions. Despite broad adoption, the importance of spatial resolution (grain and extent) over which these structural metrics are calculated remains largely unconsidered. Often researchers will quantify FSD at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 103 publications
(154 reference statements)
1
13
0
Order By: Relevance
“…However, adding spectral metrics from colour infrared photography did not systematically enhance the overall accuracies of classifying living conifers, living broadleaves or dead trees, indicating that the sole use of LiDAR metrics may suffice for separating retention trees from other trees. In a more general context for operational LiDAR‐assisted forest inventories, Atkins et al (2023) discussed the crucial issue of spatial resolution (grain and extent) over which structural metrics are derived from airborne LiDAR and how spatial scale might affect their derivation across a wide range of forest ecosystem types. The study suggested, however, that multiple spatial grain sizes may suffice for capturing the optimal scale (shown as the representative elementary area) of specific groups of forest metrics.…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
See 2 more Smart Citations
“…However, adding spectral metrics from colour infrared photography did not systematically enhance the overall accuracies of classifying living conifers, living broadleaves or dead trees, indicating that the sole use of LiDAR metrics may suffice for separating retention trees from other trees. In a more general context for operational LiDAR‐assisted forest inventories, Atkins et al (2023) discussed the crucial issue of spatial resolution (grain and extent) over which structural metrics are derived from airborne LiDAR and how spatial scale might affect their derivation across a wide range of forest ecosystem types. The study suggested, however, that multiple spatial grain sizes may suffice for capturing the optimal scale (shown as the representative elementary area) of specific groups of forest metrics.…”
Section: Thematic Groups Being Covered In the Sfmentioning
confidence: 99%
“…1. Stand-, canopy-and tree-level structural analysis by active RS data (Atkins et al, 2023;Blanchard et al, 2023;Coverdale & Davies, 2023;Hardenbol et al, 2022;Schlund et al, 2022;Singh et al, 2023;Tatsumi et al, 2022;Zhang & Liu, 2023).…”
Section: G Ener Al and S Pecific Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also no consensus about the spatial scale or grain size at which many FSD measurements should be taken, nor is there a robust statistical treatment or analysis of the role of scale (Garabedian et al, 2014). FSD metrics are often calculated at the scale of interest of a given function (Beland et al, 2019) without explicit regard given to the stability or scale‐dependency of those FSD metrics (Atkins et al, 2023). There is a clear need to understand how spatial grain and extent factor into FSD measurement.…”
Section: Current Limitations and Potential Future Directions Of Fsd M...mentioning
confidence: 99%
“…The remote sensing platforms available for measuring FSD range from small handheld devices (e.g., personal mobile device) to spaceborne platforms (Figure 2). The spatial extent and grain of a given sensor inherently influences the types of structural features it can quantify and determines the accuracy and precision of which it is capable (Atkins et al, 2023;Saatchi et al, 2011). Broadly there are two types of remote sensing, passive and active.…”
Section: Fsd Measurement Via Remote Sensingmentioning
confidence: 99%